Juridical Review of Nurse's Legal Responsibility for Patient Safety in Self Nursing Practice - Sukendar Sukendar; Aris Prio Agus Santoso; Ahmad Rifai; Sabda Wahab; Nurul Itsna Fawzi’ah (UNIFIKASI : Jurnal Ilmu Hukum, 2021)
Patient safety is the main thing in providing nursing services. Nurses must be able to ensure the ongoing patient safety program to suppress or reduce malpractice actions carried out when performing nursing services. The purpose of this study was to determine the form of legal responsibility of nurses for patient safety in independent nursing practice, and the concept of legal protection for patients as consumers of nursing service users. The approach method used in this research is a normative juridical approach, the method of collecting secondary data is that which is obtained through the literature and also sources of statutory law. Furthermore, the data were analyzed using qualitative analysis techniques. The results of the study indicate that the legal responsibility of nurses for patient safety is divided into two types of responsibilities, namely; civil liability as well as criminal liability. The application of patient protection law as a consumer includes preventive protection in the form of; services in accordance with standard operating procedures, professional standards, and standards of legislation with principles on patient safety and security as well as in the form of coaching, education, and supervision for patients. In a repressive manner in the form of; advocacy, efforts to resolve consumer protection disputes properly from the government and consumer protection institutions, in addition to compensation, compensation, and/or replacement of nursing services that are not in accordance with the agreement or not properly, as well as the implementation of justice and punishment for health care providers who has committed a error to the patient.